The Effect of Product Quality on Customer Satisfaction Implications on Customer Loyalty in the Era Covid-19 - Afriapoll Syafarudin (Ilomata International Journal of Tax and Accounting, 2021)
Customer satisfaction is the level of customer satisfaction after comparing the services or products received under what is expected. consumer satisfaction is the feeling of disappointment or pleasure for each individual after comparing the performance of the product that is thought of according to the expected product performance. Customer satisfaction is the goal of every company for the survival of every company. Paying attention to and increasing the level of customer satisfaction is very useful in the world of business competition. Companies with a high level of customer satisfaction tend to be superior to other competitors. Not only improving, but the company must also be able to maintain the stability of customer satisfaction levels to remain high. The function of customer satisfaction is very important in running a service and product business. By paying attention to customer satisfaction, entrepreneurs and business owners can find out about complaints and feedback from customers who receive services or products. From complaints and suggestions, the company can improve and improve the quality of customer service and products offered to compete and outperform competitors. A good company provides a means by which consumers can submit input and complaints so that consumers feel their voice heard. The research survey was conducted on 150 functional units at regional banks in Indonesia. The results showed that product quality affected customer quality and customer quality affected customer loyalty.